Genes related to maintenance of autophagy and successful aging - Chaves, Carolina Fioroto; Mazzotti, Diego Robles; Cendoroglo, Maysa Seabra; Ramos, Luiz Roberto; Tufik, Sergio; Silva, Vanessa Cavalcante da; D'Almeida, Vânia (Arquivos de Neuro-Psiquiatria, 2018)
Considering aging as a phenomenon in which there is a decline in essential processes for cell survival, we investigated the autophagic and proteasome pathways in three different groups: young, older and oldest old male adults. The expression profile of autophagic pathway-related genes was carried out in peripheral blood, and the proteasome quantification was performed in plasma. No significant changes were found in plasma proteasome concentrations or in correlations between proteasome concentrations and ages. However, some autophagy- and/or apoptosis-related genes were differentially expressed. In addition, the network and enrichment analysis showed an interaction between four of the five differentially expressed genes and an association of these genes with the transcriptional process. Considering that the oldest old individuals maintained both the expression of genes linked to the autophagic machinery, and the proteasome levels, when compared with the older group, we concluded that these factors could be considered crucial for successful aging.
Keywords: Autophagy; longevity; gene expression; gene networks; proteasome endopeptidase complex